2016
DOI: 10.14411/eje.2016.040
|View full text |Cite
|
Sign up to set email alerts
|

Capsazepine affects thermal preferences of the American cockroach (Blattodea: Blattidae)

Abstract: ISSN (online): 1802-8829http://www.eje.cz capsaicin induces preferences for lower temperatures in Rhodnius prolixus, while capsazepine treatment cause the opposite behaviour.The aim of our study was to assess the effect of capsazepine (TRPV1 antagonist) on the thermal preference of the American cockroach, Periplaneta americana. American cockroach has TRP receptors. Wicher et al. (2005) screened the Periplaneta cDNA library for members of the TRPC family and found a homolog of the Drosophila TRPɣ channel. It i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…On the other hand, capsaicin is often used as an insect repellent [ 46 ]. Experiments conducted on mealworm larvae and on the American cockroach using a thermal gradient showed that insects respond to capsaicin and capsazepine by modifying their thermal preferences [ 36 ; 47 ]. Mealworms intoxicated with capsaicin or capsazepine responded similarly to mammals (in mealworms, capsaicin induced preference for lower temperatures, while capsazepine for higher temperatures).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, capsaicin is often used as an insect repellent [ 46 ]. Experiments conducted on mealworm larvae and on the American cockroach using a thermal gradient showed that insects respond to capsaicin and capsazepine by modifying their thermal preferences [ 36 ; 47 ]. Mealworms intoxicated with capsaicin or capsazepine responded similarly to mammals (in mealworms, capsaicin induced preference for lower temperatures, while capsazepine for higher temperatures).…”
Section: Discussionmentioning
confidence: 99%
“…Experiments were performed in a thermal gradient using an identical method as described previously [ 36 ]. Briefly, after five days of drug administration, each individual cockroach (n = 12 for each drug) was placed in the thermal gradient trough and its thermal preferences were observed for 24 hours.…”
Section: Methodsmentioning
confidence: 99%
“…In mammals, this alkaloid has been shown to induce hypothermia that occurs both at physiological (skin vasodilation, suppression of thermogenesis and salivation) and behavioral (cold-seeking behavior) response levels [1,2,3,4]. Some reports have shown the effect of capsaicin on thermoregulatory processes in invertebrates such as an induced preference for lower temperatures in Periplaneta americana [5] or Leptinotarsa decemlineata [6]. Moreover, exposure to this alkaloid has been reported to change the responsiveness to noxious heat in the American cockroach [7] and in land snail Megalobulimus abbreviatus [8].…”
Section: Introductionmentioning
confidence: 99%
“…Kohno et al [18] demonstrated that the injection of menthol, which suppresses the activity of HsTRPA, induces bees preference for warmer regions. Zermoglio et al [22], Olszewska and Tęgowska [23] and Maliszewska and Tęgowska [5] studied the effect of capsaicin and capsazepine on insects’ thermal preferences and their results suggest the existence of structures sensitive to these substances. Detailed analysis of the effect of selected ligands on thermoregulatory processes is presented in Table 2.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation